Indeks kondisi kerang hijau (Perna viridis) dan kandungan kadmium (condition indices of green mussel, Perna viridis, and cadmium content) - Liestiaty Fachruddin; Khusnul Yaqin (Program Studi Manajemen Sumber Daya Perairan, 2019)
Green mussels (Perna viridis) are sentinel organisms that are often used in research and biomonitoring of metals. The current research aims to study the correlation between the condition index (IK) of green shells and Cadmium Metal/Shell Index. Mussels collected from Mandalle waters were 200. The length of the mussels collected was between 2.16-8.02 mm. Analysis of cadmium content in mussel tissue using Atomic Absortion Spectrophotometry (AAS). There are 10 IK formulas used in this study. One-way Pearson test was used as correlation analysis between IK and Metal/Shell Index . The results showed that IK1, IK3, IK6 correlate moderately and significantly with Metal/Shell Index. IK2 and IK9 correlate strongly and significantly with Metal/Shell Index. Other condition indices do not correlate with Metal/Shell Index statistically. These results indicate that IK2 and IK9 are IK that are sensitive to cadmium content so that they are potentially used as biomarkers. Keywords: Condition index, cadmium, simple biomarker, green mussel, Metal/Shell Index